Effect of PWM Duty Cycle and Frequency of Power Supply to the LED Bulb Efficacy - Andi Pawawoi; Wahyu Prabowo (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
In this paper described the effect of frequency and duty cycle of the PWM power supply LED bulb light efficacy. Efficacy LED bulb is measured by measuring the light flux and power consumed at standard conditions, the bulb is supplied directly from the network. Then efficacy, the luminous flux and power the bulb is also measured under the conditions given PWM power supply at some frequency and duty cycle value. In the same light flux levels between the two treatment, the use of PWM power supply can increase the efficacy of the light bulb up to 66.2%, with a value of 117.52 light efficacy lumen / Watt. At the level of light flux which is slightly lower, the use of PWM power supply to the LED bulb with a specific frequency and power supply can achieve the efficacy of 397.14 lumens / Watt